Antioxidant activity and high‐performance liquid chromatographic analysis of phenolic compounds during in vitro callus culture of Plantago ovata Forsk. and effect of exogenous additives on accumulation of phenolic compounds. (10th February 2015) - Talukder, Pratik; Talapatra, Shonima; Ghoshal, Nirmalya; Sen Raychaudhuri, Sarmistha
Abstract: BACKGROUND: Plantago ovata, commonly called psyllium, is known to be a rich source of polyphenolic compounds. The present study was aimed at determining polyphenol content and studying their antioxidant activities in P. ovata during in vitro callus culture. An attempt was also made to enhance polyphenol content using external additives. The role of PAL gene in polyphenol accumulation was also studied. RESULTS: The study indicated the presence of significant amounts of polyphenols, including flavonoids, in P. ovata callus. A gradual increase in polyphenol and flavonoid content was observed up to the third passage (63 days) of callus culture, which declined at the next passage. The third‐passage callus showed highest antioxidant activity. High‐performance liquid chromatographic results indicated the presence of high amounts of gallic acid and rutin in P. ovata calli; however, other polyphenols were also present but to a lesser extent. Additive supplementation was effective in enhancing polyphenol production and in increasing antioxidant activity in P. ovata callus. CONCLUSION: The present research reported accumulation of polyphenols in callus culture of P. ovata, which could be applied to isolation of polyphenols for various beneficial purposes. It also indicated enhancement in the production of several polyphenols and also an increase in antioxidant activity in the additive‐treated callus. © 2015 Society of Chemical Industry